Volitional action as perceptual detection: Predictors of conscious intention in adolescents with tic disorders. (March 2015) - Ganos, Christos; Asmuss, Luisa; Bongert, Jens; Brandt, Valerie; Münchau, Alexander; Haggard, Patrick
Abstract: Voluntary actions are accompanied by a distinctive subjective experience, so that they feel quite different from physically similar involuntary movements. However, the nature and origin of this experience of volition remain unclear. Voluntary actions emerge during early childhood, in parallel with reduction of involuntary movements. However, the available markers of the experience of volition, notably Libet's mental chronometry of intention, cannot readily be used in young children. In Gilles de la Tourette syndrome (GTS), however, involuntary tic movements may coexist with voluntary control into adulthood. Therefore, adolescents with GTS could potentially confuse the two classes of movement. We have measured the temporal experience of voluntary action in a well-characterised group of adolescents with GTS, and age-matched controls. We replicated previous reports of a conscious intention occurring a few hundred milliseconds prior to voluntary keypress actions. Multiple regression across 25 patients' results showed that age and trait tic severity did not influence the experience of conscious intention. However, patients with stronger premonitory urges prior to tics showed significantly later conscious intentions, suggesting that the anticipatory experience of one's own volition involves a perceptual discrimination between potentially competing pre-movement signals. Patients who were more able to voluntarily suppress their tics showed significantly earlier conscious intention, suggesting that the perceptual discrimination between different action classes may also contribute to voluntary control of tics. We suggest that the brain learns voluntary control by perceptually discriminating a special class of internal 'intentional' signals, allowing them to emerge from motor noise.